A case of pregnancy in the rudimentary horn of unicornuate uterus - Angu, Gamli; Pradhan, Arvind; Kamble, Smurti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
A unicornuate uterus with a rudimentary horn is a uterine anomaly resulting from the incomplete development of one of the Müllerian ducts and an incomplete fusion with the contralateral side. Pregnancy in a rudimentary horn of the uterus is a rare clinical condition with a reported incidence of 1 in 100,000 to 140,000 pregnancies. The majority of cases are diagnosed late, after the rupture has occurred and can present as an emergency with hemoperitonium. The use of ultrasonography helps clinicians to diagnose uterine malformations earlier, which can then be confirmed by a magnetic resonance image (MRI) or a laparoscopy. The standard treatment is the surgical excision of the horn. Our case is a gravida 2 abortion 1 patient presented at 18 weeks’ gestation with ultrasonography suggestive of fetal demise. Repeated failed attempts at induction of labour raised the suspicion of an abnormally located pregnancy. The diagnosis was confirmed at laparotomy. She underwent a laparotomy with right rudimentary horn excision. This case highlights the importance of high clinical suspicion and the need to keep an open mind about the possibilities of uterine anomalies.